THE APPOINTMENT OF MEMBERS TO THE SHARIAH ADVISORY COUNCIL OF CENTRAL BANK OF MALAYSIA: LEGAL ISSUES - Mohammad Azam Hussain; Rusni Hassan; Alias Azhar; Aznan Hasan (UUM Journal of Legal Studies, 2017)
Abstract: In Malaysia, the appointment of members to the Shariah Advisory Council (SAC) of the Central  Bank  of Malaysia (CBM) is prescribed by the Central Bank of Malaysia Act 2009 (Act 701). The Act stipulates the provisions pertaining to the eligible persons to be appointed to the SAC, procedures, terms and conditions of appointment and also remuneration and allowances for the members of the SAC. In this regard, the question arises whether the prescribed provisions are sufficient to regulate the appointment of members to the SAC and free from any shortcomings. Hence, this study sought to analyse the existing legislations governing the appointment of members to the SAC and to analyse the legal issues arising from the existing legislations. By using legal research methodology, this article analysed the entire provisions dealing with the appointment matter. Based on the data collected from statutes passed by the Parliament of and Malaysia published materials, the analytical method was used by scrutinizing the related provisions of the law pertaining to the appointment of members to the SAC. This study found that, several loopholes  exist  in  the  statutory requirement of the existing law which needs to be addressed by the respective authoritative body in order to avoid any legal conflict in the future. Hence this study is significant in order to strengthen the existing legislation governing the SAC especially related the appointment process.